Aplikace zásad strategického plánování ve veřejné správě členských států Evropské unie - Šilhánková, Vladimíra (Univerzita Pardubice, 2004)
The paper focuses on strategic planning on the local level in the European context. There are two main principles described - expert and community approach. There are good historical examples described too - East Kilbride and Rotterdam. The second part of the paper focused on contemporary approaches to strategic planning by sustainable development and Local Agenda 21. There is Berlin's LA 21 example. Last but not least there is sustainable development indicators discussed.
Keywords: strategické plánování; rozvoj měst; Udržitelný rozvoj; veřejná správa